Вміст валових та водорозчинних форм органічної речовини у ґрунті за різних способів лісокористування - Zaimenko, N.V.; Dziuba, O.I.; Bedernichek, T.Yu. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2014)
Water-base organic compounds are among the most labile fractions of soil organic matter. Their content are considered a sensitive indicator of soil quality and changes quantitatively under the influence of anthropogenic pressure. The objective of this paper was to evaluate the impacts of different felling systems on total and water extractable organic carbon content in soil. The soil samples were taken from 50 cm depth soil profile with 5 cm step. Total organic carbon (TOC), cold water extractable organic carbon (CWEOC) and hot water extractable organic carbon (HWEOC) contents in soil were determined. The highest TOC content was found in the soil under the old-growth hornbeam-oak forest: 49–63 mg/g and 12–6 mg/g in a top 0–5 cm and 0–50 cm layers respectively. Gradual, group-selection and clear felling of hornbeam were attended by significant transformations of organoprofile and decrease of TOC content especially in top 15 cm layer. However, fractional contents of cold and hot water extractable organic carbon increased with depth. The results of this research indicate that among the studied scenarios of the forest management, gradual felling caused minimal changes of soil organic matters.